Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ppul.25129
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of inpatient polysomnogram characteristics and discharge outcomes in infants with bronchopulmonary dysplasia requiring home oxygen therapy

Abstract: Rationale Little is known about the polysomnogram (PSG) characteristics in infants with bronchopulmonary dysplasia (BPD), especially severe BPD, who do not need home ventilatory support but are at increased risk for chronic hypoxia and are vulnerable to its effects. Objective This study aims to assess PSG characteristics and change in discharge outcomes in premature infants with BPD who required oxygen therapy at discharge. Methods This is a retrospective chart review of premature infants with BPD who were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(59 reference statements)
3
9
0
Order By: Relevance
“…The patients in our study were young given that the majority of patients were children with CCC(s) with SDB symptoms presenting at an early age. There are a few published studies that have retrospectively reviewed the inpatient PSGs of infants 28,32 . Kim et al reported that the most common indication for inpatient PSG in infants was persistent oxygen desaturation which is similar to our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The patients in our study were young given that the majority of patients were children with CCC(s) with SDB symptoms presenting at an early age. There are a few published studies that have retrospectively reviewed the inpatient PSGs of infants 28,32 . Kim et al reported that the most common indication for inpatient PSG in infants was persistent oxygen desaturation which is similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…This also may be a result of a paucity of normative data for OSA and CSA in infants which also may be contributing to the variability in clinical practice 33 . Similar to our study, Flores‐Fenton et al reported the main type of SDB in a cohort of infants with bronchopulmonary dysplasia was CSA with similar respiratory support management as in our study 32 …”
Section: Discussionsupporting
confidence: 82%
“…The high prevalence of nocturnal hypoxemia on recorded home oximetry suggests a potential benefit of objective monitoring of oxyhemoglobin saturation when weaning supplemental oxygen consistent with the published guideline from the American Thoracic Society. 4 There is a known increase in sleep disordered breathing in premature infants with BPD, including OSA, central sleep apnea, hypoventilation, and nonapneic hypoxemia, 21 which could explain the increased frequency of desaturation events in this cohort. It has also been reported that the severity of BPD could augment the severity of sleep disordered breathing, implying that those infants who are discharged on home supplemental oxygen therapy would be at the highest risk for clinically significant sleep disordered breathing.…”
Section: Discussionmentioning
confidence: 91%
“…There is a known increase in sleep disordered breathing in premature infants with BPD, including OSA, central sleep apnea, hypoventilation, and nonapneic hypoxemia, 21 which could explain the increased frequency of desaturation events in this cohort. It has also been reported that the severity of BPD could augment the severity of sleep disordered breathing, implying that those infants who are discharged on home supplemental oxygen therapy would be at the highest risk for clinically significant sleep disordered breathing 22 .…”
Section: Discussionmentioning
confidence: 93%
“…A recent study suggested obtaining a PSG before NICU discharge for infants with severe BPD 22 . Infants with severe BPD were often found to be hypoventilated with higher CO 2 values greater than 50 mmHg during sleep times.…”
Section: Discussionmentioning
confidence: 99%